Osmoregulated Periplasmic Glucan Synthesis Is Required for Erwinia chrysanthemi Pathogenicity - Page, Frederic (American Society for Microbiology, 2001)
Erwinia chrysanthemi is a phytopathogenic enterobacterium causing soft rot disease in a wide range of plants. Osmoregulated periplasmic glucans (OPGs) are intrinsic components of the gram-negative bacterial envelope. We cloned the opgGH operon of E. chrysanthemi, encoding proteins involved in the glucose backbone synthesis of OPGs, by complementation of the homologous locus mdoGH of Escherichia coli. OpgG and OpgH show a high level of similarity with MdoG and MdoH, respectively, and mutations in the opgG or opgH gene abolish OPG synthesis. The opg mutants exhibit a pleiotropic phenotype, including overproduction of exopolysaccharides, reduced motility, bile salt hypersensitivity, reduced protease, cellulase, and pectate lyase production, and complete loss of virulence. Coinoculation experiments support the conclusion that OPGs present in the periplasmic space of the bacteria are necessary for growth in the plant host.